THE FALL OF THE HOUSE OF USHER - SCHIZOPHRENIA - Langhoff, Darius (Acta Neophilologica, 2009)
E.A. Poe’s tale The Fall of the House of Usher features twins Roderick and Madeline who suffer from serious physical and nervous maladies. Manifestations of their mental disorders are juxtaposed in the article with the discoveries of modern psychiatry and neurology, revealing surprisingly many parallels with the clinical symptoms of schizophrenia and other related illnesses. The author of the story himself makes an impressive comparison between the characters’ split minds and the cleft in their mansion’s wall, which disrupts the architectural harmony and continu- ity of the edifice.